From Accounting to Trust: How Islamic Worldview Strengthens Financial Performance in Islamic Microfinance - Soediro, Achmad; Kusumawardani, Media; Kasyfillah, Muhammad Arta (International Review of Management and Marketing, 2026)
This study examines the influence of accounting information quality, financial reporting transparency, and financing transparency on the financial performance of Islamic Microfinance Institutions (IMFIs), while positioning the Islamic worldview as a moderating construct that embeds ethical-spiritual foundations into Islamic financial governance. Motivated by persistent challenges of weak transparency, uneven Shariah compliance, and fragmented reporting practices in IMFIs, this research integrates Islamic philosophical principles particularly tawhid, justice, maslahah, and accountability into a performance model that aligns financial viability with ethical legitimacy. Using a quantitative causal design, data were collected from 360 BMT members in Palembang, Indonesia, and analyzed through Moderated Regression Analysis (MRA). The findings demonstrate that accounting information quality, financial reporting transparency, and financing transparency each exert a positive and significant effect on financial performance. More critically, the Islamic worldview significantly strengthens all three relationships, confirming its role as a normative and operational mechanism that enhances trust, reinforces ethical accountability, and improves institutional resilience. These results provide theoretical contributions by integrating Islamic worldview into performance measurement and advancing Islamic-based accountability beyond technical metrics, while offering practical implications for strengthening governance, reporting quality, and stakeholder confidence in IMFIs. The study concludes by underscoring the inseparability of ethical accountability and financial sustainability in Islamic finance and highlights avenues for future research on non-financial outcomes and cross-regional comparisons.